L-Carnitine supplementation impairs endothelium-dependent relaxation in mesenteric arteries from rats - Valgas da Silva, Carmem P. [UNESP]; Rojas-Moscoso, Julio A.; Antunes, Edson; Zanesco, Angelina [UNESP]; Priviero, Fernanda B. M. (Informa Healthcare, 2014)
L-Carnitine (L-Car) is taken as fat burner. The risks of L-Car supplementation for the cardiovascular system are unclear. We evaluated the relaxing responses of the mesenteric and aorta rings from rats after four weeks of L-Car supplementation and/or physical training. Concentration response curves to acetylcholine (ACh) and sodium nitroprusside (SNP), as well as cyclic GMP levels, superoxide dismutase (SOD) activity and malondialdehyde (MDA) were evaluated. Physical training decreased body weight gain that was potentiated by L-Car. In mesenteric rings, L-Car impaired endothelium-dependent relaxation whereas endothelium independent relaxation was increased. In aorta, exercise improved endothelium-dependent relaxation; however, it was partially inhibited by L-Car. SNP-induced relaxation was similar in aorta of all groups. Basal cGMP were increased in aorta of exercised rats. SOD activity and MDA levels were unaltered. In conclusion, L-Car and physical exercise promotes body weight loss; however, it impairs endothelium-dependent vaso-relaxation possibly involving alterations in muscarinic receptors/eNOS/NO signalling pathway in mesenteric artery.
Keywords: Body weight; nitric oxide; physical exercise; vascular reactivity